1988
DOI: 10.1071/ea9880343
|View full text |Cite
|
Sign up to set email alerts
|

Salinity tolerance in rice varieties at different growth stages

Abstract: The salt tolerance of several Australian and overseas rice varieties was studied at germination, early vegetative growth, and reproductive development in a temperature controlled glasshouse to determine the reliability of screening at any particular stage. At all 3 stages, varieties differed in their degree of tolerance, but the order of tolerance varied considerably between stages. Of the varieties used, the Australian long grain variety Pelde was tolerant for germination but most intolerant during early vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
65
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(73 citation statements)
references
References 9 publications
8
65
0
Order By: Relevance
“…Rice has been reported to be relatively tolerant to salinity stress during germination, active tillering and towards maturity, but sensitive during early seedling and reproductive stages [23,24]. An addition of as little as 50 mM NaCl in the soil can reduce rice yield significantly [25].…”
Section: Rice Response To Salinity Stressmentioning
confidence: 99%
“…Rice has been reported to be relatively tolerant to salinity stress during germination, active tillering and towards maturity, but sensitive during early seedling and reproductive stages [23,24]. An addition of as little as 50 mM NaCl in the soil can reduce rice yield significantly [25].…”
Section: Rice Response To Salinity Stressmentioning
confidence: 99%
“…Rice genotypes show wide variations in salinity tolerance due to additive gene effects [34]. Studies indicated that rice is more resistant at reproductive and grain filling than at germination and vegetative stages [35], as well as low levels of salinity can increase the resistance of rice to higher and lethal salinity levels [36]. At present, salinity is the second type of stress and is the most predominant hindrance to rice production after drought [37].…”
Section: Effect Of Salinity Stress In Rice Cropsmentioning
confidence: 99%
“…Cultivated rice (Oryza sativa L.), a staple food for billions of people in the world, not being a halophyte is especially sensitive to salt (Gregrio et al, 1997;Munns et al, 1999). Grain yield of rice plants is reduced by 70% to 100% of its maximal yield performance by salinity (Heenan et al, 1988). Although the degree of salt tolerance of rice plants differs among species and varieties, some of them show high resistance to salinity (Yeo and Flowers, 1986) .…”
mentioning
confidence: 99%